2014
DOI: 10.3109/0142159x.2014.970998
|View full text |Cite
|
Sign up to set email alerts
|

The integrated curriculum in medical education: AMEE Guide No. 96

Abstract: The popularity of the term "integrated curriculum" has grown immensely in medical education over the last two decades, but what does this term mean and how do we go about its design, implementation, and evaluation? Definitions and application of the term vary greatly in the literature, spanning from the integration of content within a single lecture to the integration of a medical school's comprehensive curriculum. Taking into account the integrated curriculum's historic and evolving base of knowledge and theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
355
0
20

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(430 citation statements)
references
References 55 publications
8
355
0
20
Order By: Relevance
“…Current issues and regulations regarding the importance of patientphysician relation, informed consent, malpractice, research planning, medical ethics and occupational safety should be added to the curriculum and change in education should be continuous in order to keep up with the advancements in the world by also considering the requirements of the country. It is suggested that core curriculum takes two thirds of the education period and the remaining one third is devoted to areas for detailed further study of topics selected by the student [6][7][8][9].…”
Section: Overview Of Pre-graduate Medical Educationmentioning
confidence: 99%
“…Current issues and regulations regarding the importance of patientphysician relation, informed consent, malpractice, research planning, medical ethics and occupational safety should be added to the curriculum and change in education should be continuous in order to keep up with the advancements in the world by also considering the requirements of the country. It is suggested that core curriculum takes two thirds of the education period and the remaining one third is devoted to areas for detailed further study of topics selected by the student [6][7][8][9].…”
Section: Overview Of Pre-graduate Medical Educationmentioning
confidence: 99%
“…In this letter we identify the current challenges and opportunities associated with integrated curriculum particularly in the aspects of diminishing basic science courses, need of improvised implementation strategies and gaps in clinical practice of first and second year program of medical or allied health science program. 3,4 In addition, we also provide brief information on pros and cons associated with integrated teaching. In our view, the most common disadvantage associated with integrated curriculum is diminished basic science coursesin curriculum of health sciences programs like anatomy, physiology, biochemistry, microbiology (for medical and allied program), and organic chemistry, physical chemistry, professionalism, social sciences etc.…”
Section: Dear Editormentioning
confidence: 99%
“…The operationalization of the curriculum generates an educational context [15] that should ideally promote an autonomous, self-motivated, independent, problem-solving learner. Since the early 1990s, a major trend in medical curricula around the world has been about integrating the teaching of basic, clinical and psychosocial sciences [20]. The principle is to construct multidisciplinary system-based blocks integrating discipline-based threads [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The principle is to construct multidisciplinary system-based blocks integrating discipline-based threads [21,22]. By breaking down the barriers between basic and clinical sciences, integrated curricula are thought to promote knowledge retention and development of clinical skills [20]. They also aim at providing an opportunity for students to acquire a more relevant and less fragmented knowledge.…”
Section: Introductionmentioning
confidence: 99%